An equitable and scalable approach to track fidelity of implementation in partnership with teachers - Spacciapoli, Megan; Viana, Mara; Saunders Wilder, Oliver; Sullivan, Jillian; McCallum, Tia; Wilder-Smith, Barbara (Frontiers in Education, 2022)
Social and emotional learning (SEL) is a key focus of early childhood education. A significant body of research demonstrates the critical impact of fidelity of SEL curriculum and intervention implementation on child outcomes; however, few widely-used curricula regularly assess classroom-level implementation fidelity outside of the context of research or correlate fidelity with key areas of children’s development of these skills. Fidelity measurement often focuses on easy-to-quantify variables such as classroom environment or lesson plan adherence, and is a periodic snapshot used as a moderator or co-variate when assessing child outcomes, rather than being intentionally leveraged as a systematic, ongoing process to evaluate and support implementation. In this paper, we present a novel approach to capturing fidelity data as a core component of professional development. We outline our findings from a pilot of our approach using short, teacher-recorded videos submitted across the school year as a vehicle for capturing and sharing real-time data related to professional learning, implementation, and curricula impact, as well as a framework for building equitable partnerships with teachers. Results from the initial pilot of this approach in several hundred classrooms across the US demonstrate feasibility and utility and suggest that teacher-recorded videos can offer a scalable means to collect continuous samples of fidelity data, providing a richer view of professional learning, while simultaneously creating the opportunity to provide ongoing feedback and engage teachers in partnership in reflecting on practice and its impact on children’s development. We developed and piloted an approach where teachers record and upload videos of teaching practices and children engaging with their peers in specific classroom activities via a mobile application. Each video submission has a focal activity and associated set of indicators which are shared with teachers in advance to create an equitable feedback system in which both curriculum staff and teachers engage in reflecting on children’s interactions and the application of the curricular approach in their classroom. Videos are viewed and coded on these sets of indicators by both the teachers and curricular coaches who provide targeted feedback in an interactive exchange on a dashboard accessible by teachers and their curricular coach.